Melek Digital untuk Santri: Pelatihan Literasi Digital dan Etika Bermedia Sosial di Pondok Pesantren Sunan Drajat Lamongan - Biyati Ahwarumi (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This article aims to improve the digital literacy and media da'wah skills of students at the Sunan Drajat Islamic Boarding School through community-based training. The activity was carried out for three days with a participatory approach, involving 30–50 final year students. The training methods included interactive lectures, simulations, content production practices, and evaluations through pre-tests, post-tests, questionnaires, and digital portfolios. The results showed a significant increase in digital literacy scores, increased awareness of media ethics, and the ability of students to produce creative and moderate da'wah content. The collective account @santrisundra is evidence of the active involvement of students in digital da'wah. This program shows that the integration of digital literacy in Islamic boarding school education is effective in forming students who are capable, wise, and responsible in facing the challenges of the digital world. Keywords: Digital literacy, Students, Islamic boarding schools, Media ethics, Digital da'wah